Effects of agitation speed, temperature, carbon and nitrogen sources on the growth of recombinant Lactococcus lactis NZ9000 carrying domain 1 of aerolysin gene - Ibrahim, Siti Balkhis; Abdul Rahman, Nor'aini; Mohamad, Rosfarizan; Abdul Rahim, Raha (Academic Journals, 2010)
Lactococcus lactis is a Gram-positive bacterium widely used in the production of buttermilk and cheese. Recently, the bacterium becomes famous as the genetically modified organism can be used alive for the treatment of disease. In this study, different cultural conditions based on agitation speed and temperature on the growth of recombinant L. lactis NZ9000 harboring domain 1 of aerolysin gene (NHD1Aer) were investigated using shake flask experiment. The effect of different carbon (glucose, sucrose and lactose) and nitrogen (yeast extract, peptone, NH4 Cl, (NH 4)2SO4, and urea) sources in M17 medium on the cell accumulation were also tested. The results showed that the highest cell concentration (3.22 g/L, μm= 0.58 h-1) was obtained when the cultivation was incubated at 27°C and at agitation of 100 rpm. The cells growth was markedly improved when utilizing glucose and peptone/yeast extract as carbon and nitrogen sources, respectively. The aerolysin gene in the cells after four generation time was extracted and then analyzed using agarose gel electrophoresis. The results obtained showed a 250 bp band amplified of domain 1 of the aerolysin gene.